ANALISIS KEBERHASILAN PROGRAM PERTANIAN TERPADU DI KECAMATAN PULAU SEBUKU, KABUPATEN KOTA BARU, PROVINSI KALIMANTAN SELATAN - Hermanawati, Erni (Jurnal Online Pertanian Tropik, 2015)
Evaluation of agricultural programs is necessary to determine the level of success of an agricultural program. The objective is to evaluate the research in the integrated farming program implemented in five villages in the District of Pulau Sebuku and to create a better and sustainable alternative model of the integrated farming application. The evaluation uses a multicriteria analysis method to make the criteria and indicators of integrated farming principles. It can be concluded that not all of the criteria can be accepted. Out of 10 criteria, one criterion namely environmental goals can be accepted (with score â‰¥ 3) in the five villages. Two criteria namely the economic purpose and land management can be accepted in four villages. The next two criteria namely social objectives and marketing support can be accepted in two villages. Two other criteria, namely waste management and climate/weather management can only be accepted by one village. Three criteria have not been acceptable to all villages, namely crop management, cattle management, and institutional management. The analysis indicates a lack of institutional function, knowledge, and technology in integrated farming among community. Efforts to improve the program by establishing agricultural institutions, human resource development as well as ease of access to saprodi and marketing facilities. The involvement of all parties including the community, the government, the private sector and NGOs is needed to achieve the expected success of integrated farming.